Crossing Power Borders in a Tight Silk Suit: Loci of Power in A troche y moche by Gustavo Sainz - Carpenter, Victoria (Revista Canadiense de Estudios Hispánicos, 2022)
This study considers how the fluidity of power loci, in terms of text ownership, replaces the static nature of hegemonic relationships between the protagonist and the characters in Gustavo Sainz’s novel A troche y moche (2002). The key aspect of this study of power loci and power border crossing is the analysis of the complexity of the dominance/subordination dichotomy. Using the theories of hegemonic masculinity and posthegemony, the essay examines the fluid nature of borders between the power loci of the writer-protagonist, his associates, and his kidnappers.